2016
DOI: 10.1021/acs.langmuir.6b01356
|View full text |Cite
|
Sign up to set email alerts
|

Sponge Phases and Nanoparticle Dispersions in Aqueous Mixtures of Mono- and Diglycerides

Abstract: The lipid liquid crystalline sponge phase (L3) has the advantages that it is a nanoscopically bicontinuous bilayer network able to accommodate large amounts of water and it is easy to manipulate due to its fluidity. This paper reports on the detailed characterization of L3 phases with water channels large enough to encapsulate bioactive macromolecules such as proteins. The aqueous phase behavior of a novel lipid mixture system, consisting of diglycerol monooleate (DGMO), and a mixture of mono-, di- and triglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 46 publications
9
68
0
Order By: Relevance
“…This effect is rather pronounced at high P80 concentrations, where even the loss of internal particle structure can occur. 22,25 In our earlier work 13 with the same DGMO/GMO-50/P80/water system as studied here, we were also able to form nanoparticles with highly swollen sponge phase structures over a wider range than in the pure lipid-aqueous system. Cryo-TEM imaging showed that such phases could be dispersed into sponge-like nanoparticles (L 3 -NPs) that featured a dense sponge phase core with swollen bilayer structures at the interface.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…This effect is rather pronounced at high P80 concentrations, where even the loss of internal particle structure can occur. 22,25 In our earlier work 13 with the same DGMO/GMO-50/P80/water system as studied here, we were also able to form nanoparticles with highly swollen sponge phase structures over a wider range than in the pure lipid-aqueous system. Cryo-TEM imaging showed that such phases could be dispersed into sponge-like nanoparticles (L 3 -NPs) that featured a dense sponge phase core with swollen bilayer structures at the interface.…”
Section: Introductionsupporting
confidence: 56%
“…The q 1 value was found to be 0.05 Å À1 , which agrees quite well with the SAXS results where q 1 was 0.047 Å À1 . It should be noted that, in spite of the fact that the dP80 and hP80 used here were from a different batch than the hP80 used for the SAXS and cryo-TEM experiments, 13 we still found similar sponge phases in terms of dimensions and location in the phase diagram. Comparing different solvent contrast, it can be seen that in H 2 O the repeat distances are larger than in D 2 O, as q 1 shift towards lower q-values, both for dP80 and hP80.…”
Section: View Article Onlinementioning
confidence: 59%
See 2 more Smart Citations
“…The latter were evidenced by smooth SAXS curves typical for sponge-type lipid particles. 90,92 The presence of Braggs peaks in Figure 2a,b characterized the nanocarriers with a periodic inner organization (cubosomes). The determined lattice parameters of the coexisting cubic unit cells in the Pn3m cubosome particles are a 1 = 21.1 nm and a 2 = 16.4 nm ( Figure 2b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%